ダイ 29 ジ ナンキョク チイキ カンソク タイ ショウワ キチ エットウ ホウコク 1988-1989 - 渡辺, 興亜; ワタナベ, オキツグ; Watanabe, Okitsugu (1991)
P(論文) 第29次南極地域観測隊越冬隊は37名により構成された。うち27名は昭和基地において越冬観測に従事し, 残り10名はあすか観測拠点において2年目の越冬観測を行った。あすか観測拠点における活動はすでに別に報告されているので, ここでは昭和基地における活動を報告する。昭和基地の活動は1988年2月1日, 基地を引き継いでより, 1989年1月31日まで続けられた。その間, 定常観測のほかに第29次南極地域観測隊研究観測計画に基づいて観測を実施した。気水圏系による「南極における気候変動に関する総合研究(第2年次)」と生物・医学系による「陸上生態系構造の研究(第2年次)」などである。そのほか宙空系によるオーロラ観測や雪氷・地学系によるテレメトリーによる地震観測も実施された。また設営面では通常の基地を維持する活動のほか, 基地の整備にも努めた。1987年10月以降無人となったみずほ基地の維持も行った。 The wintering party of the 29th Japanese Antarctic Research Expedition perfomed its activities at two wintering sites from 1988 to 1989,consisting of 27 members at Syowa Station (69°00′S, 39°35′E)(leader : Okitsugu WATANABE) and 10 members at Asuka Station (71°31.5′S, 24°8.3′E)(leader : Keizo YANAI). Scientific and logistics activities at both wintering stations are reported separately. Wintering activities at Asuka Station have already been reported by K. YANAI (Nankyoku Shiryo, 34,394,1990). The main scientific research programs at Syowa Station were as follows : 1) Development of unmanned geophysical observatory (upper atmosphere physics). 2) Clouds and precipitation observation by means of vertical radar carried out as a part of Antarctic Climate Research Program (ACR)(lower atmosphere physics). 3) Biological investigation of Antarctic terrestrial ecosystem (biological science), part of international Biological Investigations of Terrestrial Antarctic Systems (BITAS). Routine and fundamental geoscience were performed as in preceding years. departmental bulletin paper